Drinking and driving among adults in the United States: Results from the 2012–2013 national epidemiologic survey on alcohol and related conditions-III. (April 2019) - Fan, Amy Z.; Grant, Bridget F.; Ruan, W. June; Huang, Boji; Chou, S. Patricia
Highlights: Men had greater rates of driver-based and passenger-based alcohol-impaired driving (A-ID) than women. Rates of driver-based and passenger-based A-ID practices were greater among those 18–29 and 35–44 years old. Rates of driver-based and passenger-based A-ID were greater among Whites/Blacks/Native Americans and the rate of driver-based A-ID was greater among those with higher education/income. Driving under the influence of alcohol and passenger-based A-ID remains a public health problem in the US. There is a need for monitoring of A-ID practices and the development of targeted prevention/intervention programs. Abstract: Despite the seriousness of alcohol-impaired driving (A-ID) very few national surveys on reported A-ID have been conducted since the early 2000s. This study examined 12-month prevalences of driver-based A-ID and passenger-based alcohol-related practices in a large representative sample of the U.S. population. Twelve-month prevalences of drinking while driving and driving after drinking too much were 5.7% and 3.9%, respectively. Corresponding prevalences of having an accident while intoxicated and having an accident with an injury while intoxicated were 0.6% and 0.2%, respectively. Twelve-month prevalences of riding as a passenger with a drinking driver and riding as a passenger while drinking were 7.0% and 10.7%, respectively. In general, sociodemographic characteristics of individuals more vulnerable to all of these A-ID practices were similar: men, Whites, Blacks and Native Americans, younger and middle-aged adults, upper socioeconomic status, being never or previously married, and residing in the Midwest. Results of this study underscore the importance of assessing driver-based A-ID and passenger-based alcohol-related practices and the need to target prevention and intervention programs to reduce these practices among those subgroups of the U.S. population most vulnerable to them.